Motor Vehicles Air Pollution in Nairobi, Kenya - Odhiambo, G.; Kinyua, A.; Gatebe, C.; Awange, Joseph (Maxwell Science Publication, 2010)
Air quality monitoring in most developing countries is not routinely conducted, and in some urban areas such information does not even exist, though signs of deteriorating air quality and health problems related to air pollution are visible. By measuring air pollutants (i.e., Nitrogen Oxides, ozone, suspended particulates matter (PM10), and trace elements e.g. lead), this study investigated air quality in Nairobi, one of the largest cities in eastern Africa and the capital of Kenya. Sampling was done once a week from February to April 2003. Hourly average concentrations of NOx and O3 were measured using a technique that is based on "chemilumiscent" reaction at a site connecting two main highways in Nairobi (University and Uhuru) from 9:00 a.m. to 5:00 p.m. PM10 was collected using “Gent” Stacked Filter Unit (SFU) air sampler fitted with nucleopore filters (0.4 and 8.0 mm pore size for fine and coarse filters, respectively) that were analyzed for trace elements by Energy Dispersive X-ray Fluorescent (EDXRF) technique.An automatic vehicle counter was used for determining the vehicle density at the sampling site. Results show that most pollutants, for example, lead (0.051 to 1.106 μg/m3), bromine (LLD to 0.43 μg/m3), NO2 (0.011-0.976 ppm), NO (0.001-0.2628 ppm) and O3 (LLD-0.1258 ppm) are within the WHO guidelines. PM10 levels (66.66 - 444.45 μg/m3) were above the WHO guidelines for most of the days, with coarse particulate accounting for more than 70%. Strong correlation (r = 0.966) between fine (0.4 μm) particulates, NOx, and motor vehicle density, indicate the importance of traffic as a common source for both fine particulates and NOx.